2018
DOI: 10.3892/br.2018.1161
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of progesterone on nitric oxide/cyclic guanosine monophosphate signaling and contraction in gastric smooth muscle cells

Abstract: Previous studies have shown that progesterone could inhibit muscle contraction in various sites of the gastrointestinal tract. The underlying mechanisms responsible for these inhibitory effects of progesterone are not fully known. The aim of the current study was to investigate the effect of progesterone on the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) pathway and muscle contraction in the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…We also sought to explore the change in estrogen effect on NO/cGMP pathway in the stomach muscle cells during pregnancy. This research in pregnant GMSC is in continuation of our previously reported effect of estrogen and progesterone in nonpregnant female [30, 31]. Our findings may be of considerable importance in understanding the cause of the various pregnancy-associated GI tract motility disorders and would further pave the way for understanding the ER-mediated smooth muscle contraction-relaxation pathways and thereby establishing novel therapeutic approaches for treatment of GI disorders.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also sought to explore the change in estrogen effect on NO/cGMP pathway in the stomach muscle cells during pregnancy. This research in pregnant GMSC is in continuation of our previously reported effect of estrogen and progesterone in nonpregnant female [30, 31]. Our findings may be of considerable importance in understanding the cause of the various pregnancy-associated GI tract motility disorders and would further pave the way for understanding the ER-mediated smooth muscle contraction-relaxation pathways and thereby establishing novel therapeutic approaches for treatment of GI disorders.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, estrogen induces relaxation of vascular smooth muscle by a process that involves activation of NO-cGMP pathway [29]. Most importantly, we recently reported estrogen- and progesterone-induced relaxation in stomach smooth muscle cells via activation of the NO-cGMP pathway [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown that progesterone inhibits intestinal smooth muscle cells mainly by increasing nitric oxide synthesis to induce smooth muscle relaxation. In addition, progesterone can inhibit signaling pathways that mediate contraction, such as Rho kinase [ 42 , 43 ]. Hermoso and Villalo found that interstitial ICC not only expresses connexin Cx43, but also that the level of sex hormones affect the expression and function of connexin [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increase in NO level can cause the smooth muscles in the eye to relax [47]. Nitric oxide is synthesized from L-arginine by NO synthase and is known to relax vascular smooth muscle through the elevation of cGMP that, in turn, mediates a relaxation response [38,[48][49][50][51]. NO synthase has been found in ciliary muscle and other ocular tissues [52].…”
Section: Discussionmentioning
confidence: 99%
“…Targets of CC. The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP, https://old.tcmsp-e.com/tcmsp.php) was utilized to screen active ingredients of CC by using "Juhua," "Juemingzi," "Gouqizi," "Huangjing," "Nvzhenzi," and "Mohanlian" as keywords, with the criteria OB ≥ 30% and DL ≥ 0:18 [38].…”
Section: Screening the Effective Components And Potentialmentioning
confidence: 99%